Lithium ion battery diaphragm containing modified halloysite nanotube, preparation method of lithium ion battery diaphragm and lithium ion battery

By combining modified elolite nanotubes with polybenzimidazole, a lithium-ion battery separator with regular finger holes and sponge holes was prepared, which solved the problem of thermal shrinkage of polyolefin separator and disorderly growth of lithium dendrites at high temperatures, and achieved higher battery safety and electrochemical performance.

CN119601892APending Publication Date: 2025-03-11SHENZHEN ACAD OF METROLOGY & QUALITY INSPECTION +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411403565.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing polyolefin lithium-ion battery separators are prone to heat shrinkage at high temperatures, the anode lithium dendrites have severe disordered growth, poor high-temperature cycle stability, large electrode polarization, and the windows of conductivity, electrolyte wetting, flame retardant and electrochemical stability are not ideal.

Method used

Modified ellowite nanotubes (sulfonated litlowite nanotubes, sHNT-Li) and polybenzimidazole (OPBI) were combined with polybenzimidazole (OPBI) to prepare a lithium-ion battery separator through a non-solvent phase transfer method to form a microscopic pore structure composed of regular finger holes and sponge holes.

Benefits of technology

It improves the heat resistance, conductivity and electrolyte wetting of the separator, inhibits the disorderly growth of lithium dendrites, improves the safety of use and electrochemical performance of the battery, and especially shows excellent charging and discharge stability and low electrode polarization at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601892A_ABST
    Figure CN119601892A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a lithium ion battery diaphragm containing modified halloysite nanotubes, a preparation method of the lithium ion battery diaphragm and a lithium ion battery, and the preparation method comprises four steps which are shown in Figure 1 in Figure 1 in Figure 1 in the specification. According to the invention, the sulfonated lithiated halloysite nanotube (sHNT-Li) is introduced into the battery diaphragm, so that the affinity between the diaphragm and an electrolyte is increased, and more sites and channels are provided for lithium ion transmission; and sHNT-Li is utilized to change the diffusion force in the process of a non-solvent phase conversion method, so that the high-temperature-resistant lithium ion battery diaphragm with a microscopic pore channel structure consisting of regular finger-shaped pores and spongy pores is obtained. The diaphragm electrolyte is good in wettability, high in conductivity, good in electrochemical stability and good in lithium dendrite inhibition effect. The battery assembled by the diaphragm shows excellent specific discharge capacity, cycling stability and rate capability, and especially has excellent charge-discharge stability at high temperature; in addition, the electrode polarization degree of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery separator containing modified halloysite nanotubes, a preparation method thereof, and a lithium ion battery. Background Art

[0002] The separator is one of the core components of lithium-ion batteries (LIBs). Its function is to separate the positive electrode from the negative electrode to prevent the battery from short-circuiting and causing safety accidents. At the same time, it ensures that lithium ions can pass through the microporous channels normally during charging and discharging to ensure the normal operation of the battery. The performance of the separator directly affects the safety, capacity, rate, life and other performance of the battery.

[0003] Polyolefin separators, such as polyethylene (PE) separators, polypropylene (PP) separators, and PE / PP composite films, are the mainstream products in the current separator market, and the production processes are mainly dry and wet. Due to the limitations of material properties and production processes, polyolefin separators still face several problems in the application process: First, the melting point of polyolefin materials is low, so polyolefin separators have poor heat resistance and are prone to thermal shrinkage at high temperatures, which leads to battery short circuits, and then causes dangerous events such as lithium battery fires and explosions; second, the conductivity, electrolyte wettability, flame retardancy, and electrochemical stability window of polyolefin separators are not ideal; third, the lithium dendrites of batteries assembled with polyolefin separators grow severely during service, and lithium dendrites easily pierce the separator, causing micro-short circuits of lithium batteries, causing safety hazards to lithium batteries; fourth, the cycle stability of batteries assembled with polyolefin separators at high temperatures (such as 50°C, 90°C) is very poor; fifth, the polarization of battery electrodes assembled with polyolefin separators is relatively large.

[0004] In order to improve the safety of use and electrochemical performance of lithium batteries, some materials are coated on the surface of polyolefin diaphragms through different coating processes to form coated polyolefin diaphragms; the coated diaphragms on the market mainly include inorganic coated diaphragms, organic coated diaphragms, and organic + inorganic coated diaphragms. The coating materials used in this type of coated diaphragms usually have good heat resistance. However, the base material under the coating often shrinks at high temperatures, resulting in the collapse of the overall structure of the diaphragm. Therefore, this modification scheme based on polyolefin diaphragms cannot fundamentally solve the problem of heat resistance of the diaphragm, and cannot fundamentally solve the safety of lithium batteries. In addition, the growth of anode lithium dendrites in lithium batteries assembled with this type of coated polyolefin diaphragm is still relatively serious during the charge and discharge cycle. As we all know, coating also causes some negative effects, such as increased diaphragm thickness and body resistance (R b ) increases, the charge / discharge efficiency decreases, etc.

[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a lithium ion battery separator containing modified halloysite nanotubes, a preparation method thereof, and a lithium ion battery, aiming to solve the following problems: the existing polyolefin separators are prone to thermal shrinkage at high temperatures; the lithium dendrites on the anode surface of the lithium ion battery assembled with the existing polyolefin separators have serious disordered growth; the lithium ion battery assembled with the existing polyolefin separators has poor high-temperature cycle stability; the lithium ion battery assembled with the existing polyolefin separators has large electrode polarization; the electrical conductivity, electrolyte wettability, flame retardancy, electrochemical stability window, etc. of the polyolefin separators are not ideal.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing a lithium ion battery separator containing modified halloysite nanotubes comprises the following steps:

[0009] providing an OPBI solution and a solution of sulfonated lithiated halloysite nanotubes (sHNT-Li);

[0010] Mixing the OPBI solution and the sulfonated lithiated halloysite nanotube (sHNT-Li) solution to obtain a mixed solution;

[0011] The mixed solution is coated on a substrate, and the solvent in the mixed solution is removed to obtain a lithium ion battery separator containing sulfonated lithiated halloysite nanotubes (sHNT-Li).

[0012] The method for preparing a lithium-ion battery separator containing modified halloysite nanotubes is characterized in that the modified halloysite nanotubes are sulfonated lithiated halloysite nanotubes (sHNT-Li), and the sulfonated lithiated halloysite nanotubes (sHNT-Li) are obtained by first sulfonating the halloysite nanotubes and then performing lithiation modification.

[0013] The method for preparing a lithium-ion battery separator containing modified halloysite nanotubes, wherein the solvent of the solution of sulfonated lithiated halloysite nanotubes (sHNT-Li) and the solvent of the OPBI solution are jointly selected from one or more of N-methylpyrrolidone, dimethyl sulfoxide, and N,N-dimethylacetamide.

[0014] The method for preparing a lithium-ion battery separator containing modified halloysite nanotubes, wherein in the mixed solution, the mass ratio of the sHNT-Li to the OPBI is 10%-50%.

[0015] The method for preparing a lithium-ion battery separator containing modified halloysite nanotubes, wherein the preparation process of the sulfonated lithiated halloysite nanotubes (sHNT-Li) is as follows: first, the halloysite nanotubes (HNTs) are acid-activated using hydrochloric acid (HCl); then, the acid-activated halloysite nanotubes (HNTs) are mixed with 3-chloropropyltrimethoxysilane (CPTMS) to obtain HNT-Cl; then, the HNT-Cl is reacted with tannic acid (TA) to obtain a sulfonated product sHNT; finally, the sHNT is soaked in hydrochloric acid (HCl) and reacted with a lithium hydroxide (LiOH) solution to obtain the product sHNT-Li.

[0016] The method for preparing the lithium-ion battery separator containing modified halloysite nanotubes, wherein the mixing treatment is continuous stirring at 60-100° C. for 15-24 hours.

[0017] The method for preparing the lithium-ion battery separator containing modified halloysite nanotubes, wherein the method for removing the solvent in the mixed solution is: placing the substrate coated with the mixed solution in anhydrous methanol for immersion treatment, and the immersion treatment is standing at room temperature for 8-15 minutes.

[0018] A lithium ion battery separator containing modified halloysite nanotubes is prepared by using the lithium ion battery separator preparation method (non-solvent phase transfer method), and the microscopic pores of the separator are composed of regular finger-like pores and sponge-like pores.

[0019] The lithium-ion battery separator containing modified halloysite nanotubes has a thickness of 20-40 microns.

[0020] A lithium ion battery comprises a positive electrode sheet, a negative electrode sheet and a lithium ion battery separator containing modified halloysite nanotubes; the lithium ion battery separator containing modified halloysite nanotubes is located between the positive electrode sheet and the negative electrode sheet.

[0021] Beneficial effects: The present invention provides a lithium ion battery separator containing modified halloysite nanotubes, a preparation method thereof, and a lithium ion battery. The preparation method comprises the steps of: providing an OPBI solution and a solution of sulfonated lithiated halloysite nanotubes (sHNT-Li); mixing the OPBI solution and the solution of sulfonated lithiated halloysite nanotubes (sHNT-Li) to obtain a mixed solution; coating the mixed solution on a substrate, and removing the solvent in the mixed solution to obtain a lithium ion battery separator containing sulfonated lithiated halloysite nanotubes (sHNT-Li); and assembling a lithium ion battery using the lithium ion battery separator containing sulfonated lithiated halloysite nanotubes (sHNT-Li). The present invention introduces sulfonated lithiated halloysite nanotubes (sHNT-Li) into the battery separator, thereby increasing the affinity between the separator and the electrolyte, and providing more sites and microscopic channels for the transmission of lithium ions; the sulfonated lithiated halloysite nanotubes (sHNT-Li) are used to change the diffusion force in the non-solvent phase transformation process to obtain a high-temperature resistant lithium-ion battery separator with a microscopic pore structure consisting of regular finger-like pores and sponge-like pores. The separator has good wettability to the electrolyte, high electrical conductivity, and good electrochemical stability. The unique pore structure can induce lithium ions to pass through the separator more quickly and deposit evenly on the surface of the lithium metal anode, effectively inhibiting the disordered growth of lithium dendrites, and improving the safety and electrochemical performance of lithium-ion batteries. The battery assembled using the separator exhibits excellent discharge specific capacity, cycle stability, and rate performance, especially excellent charge and discharge stability at high temperatures; in addition, the battery electrode polarization degree is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic flow chart of a method for preparing a lithium-ion battery separator containing modified halloysite nanotubes according to the present invention;

[0023] Figure 2 Schematic diagram of lithium ion transport in a battery assembled with sHNT-Li composite separator;

[0024] Figure 3 XPS spectra of HNTs, sHNT, and sHNT-Li;

[0025] Figure 4 TEM images of HNTs and sHNT-Li;

[0026] Figure 5 TEM and EDS images of sHNT-Li;

[0027] Figure 6 TGA curves (a) and FT-IR spectra (b) of HNTs and sHNT-Li, TGA curve of the separator (c), and FT-IR spectra of the separator and sHNT-Li (d);

[0028] Figure 7 SEM images of PP film, OPBI film, OPBI@HNT20 composite film, OPBI@sHNT-Li10 composite film, OPBI@sHNT-Li20 composite film, and OPBI@sHNT-Li30 composite film;

[0029] Figure 8 Results of anti-bending, electrolyte wettability, and contact angle of PP film, OPBI film, OPBI@HNT20 composite film, OPBI@sHNT-Li10 composite film, OPBI@sHNT-Li20 composite film, and OPBI@sHNT-Li30 composite film;

[0030] Fig. 9 Heat resistance of PP film, OPBI film, OPBI@HNT20 composite film, OPBI@sHNT-Li10 composite film, OPBI@sHNT-Li20 composite film, and OPBI@sHNT-Li30 composite film (a); flame retardancy of PP film and OPBI@sHNT-Li20 composite film (b);

[0031] Fig.10 The AC impedance of a battery assembled by a separator sandwiched between two steel plates (a), the interfacial resistance of a symmetrical battery assembled by a separator sandwiched between two lithium electrodes (b), the linear sweep voltammetry (LSV) test results of a battery assembled by a lithium iron phosphate positive electrode and a separator sandwiched between steel plates (c), and the lithium deposition / stripping cycle stability of a battery assembled by a separator sandwiched between two lithium electrodes (d);

[0032] Fig.11 The SEM image of the pure lithium sheet surface (a), the SEM image of the anode lithium sheet surface of the battery assembled with PP film, OPBI film, and OPBI@HNT20 composite film after 200 charge and discharge cycles (bd), and the schematic diagram of lithium ion deposition and lithium dendrite growth on the anode lithium sheet surface in the battery assembled with PP film and OPBI@HNT20 (e);

[0033] Fig.12 The charge and discharge curves of the battery assembled with PP diaphragm and OPBI@sHNT-Li20 composite diaphragm (a, b), and the cycle stability and rate performance of LiPO4 / Li half-cell (c, d);

[0034] Fig.13 The discharge curves of the battery assembled with PP separator and OPBI@sHNT-Li20 composite separator at 0.5C at 50℃ and 90℃. DETAILED DESCRIPTION

[0035] The present invention provides a lithium ion battery separator containing modified halloysite nanotubes and a preparation method thereof, and a lithium ion battery. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0036] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as generally understood by those skilled in the art in the art to which the present invention belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless specifically defined as herein.

[0037] like Figure 1 As shown, the present invention provides a method for preparing a lithium ion battery separator containing modified halloysite nanotubes and a lithium ion battery, comprising the steps of:

[0038] Step S10: providing an OPBI solution and a solution of sulfonated lithiated halloysite nanotubes (sHNT-Li);

[0039] Step S20: mixing the OPBI solution and the sulfonated lithiated halloysite nanotube (sHNT-Li) solution to obtain a mixed solution;

[0040] Step S30: coating the mixed solution on a substrate, and removing the solvent in the mixed solution to obtain a lithium-ion battery separator containing sulfonated lithiated halloysite nanotubes (sHNT-Li);

[0041] Step S40: Assembling a lithium-ion battery using the lithium-ion battery separator containing sulfonated lithiated halloysite nanotubes (sHNT-Li).

[0042] In this embodiment, polybenzimidazole (OPBI) is a polymer with excellent thermal stability and mechanical properties. Since the OPBI molecular chain contains polar ether bonds and pyridine structures, it can enhance the affinity with the electrolyte. Therefore, it is prepared into a polymer membrane for lithium-ion batteries, which can improve the safety and electrochemical performance of the battery. HNTs have excellent mechanical properties, large specific surface area, pore volume, excellent hydrophilicity and easy functionalization, and can be used as one of the good choices for polymer doping materials. Halloysite nanotubes (HNTs) are modified by sulfonation and lithium to obtain sulfonated lithium halloysite nanotubes (sHNT-Li). sHNT-Li is introduced into the membrane to increase the affinity between the membrane and the electrolyte, and at the same time provide more sites and microscopic channels for the transmission of lithium ions; sulfonated lithium halloysite nanotubes (sHNT-Li) are used to change the diffusion force in the non-solvent phase conversion process to obtain a high-temperature resistant lithium-ion battery separator with a microscopic pore structure composed of regular finger-like pores and sponge-like pores.

[0043] Specifically, in view of the characteristics of polybenzimidazole and sHNT-Li, the two are composited into a lithium-ion battery separator and applied to lithium-ion batteries, which helps to solve the safety problems of lithium-ion batteries caused by the heat resistance, flammability and disordered growth of lithium dendrites of the separator. At the same time, from the perspective of the separator, the electrochemical properties of lithium-ion batteries such as rate and cycle stability (including room temperature and high temperature) are improved, and the polarization of battery electrodes is reduced. Experimental data show that compared with commercial polyolefin separators, the lithium-ion battery composite separator prepared by the non-solvent phase separation process has excellent heat resistance, flame retardancy and the effect of inhibiting the disordered growth of lithium dendrites, which can effectively improve the safety of lithium-ion batteries. At the same time, the lithium-ion battery separator exhibits higher ionic conductivity (1.82mS cm -1 ) and electrolyte absorption rate (397%). The peak discharge capacity of the LiFePO4 / Li battery assembled with the lithium-ion battery separator at 0.5C is 150.2 mAh g -1 After 200 cycles, the capacity retention rate of the battery is 91.7%. In addition, the LiFePO4 / Li battery assembled with the lithium-ion battery separator can also operate at temperatures of 50°C and 90°C and has a considerable capacity retention rate.

[0044] In some embodiments, the solvent of the solution of sulfonated lithiated halloysite nanotubes (sHNT-Li) and the solvent of the OPBI solution are jointly selected from but not limited to one or more of N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), and N,N-dimethylacetamide; the solvents of the solution of sulfonated lithiated halloysite nanotubes (sHNT-Li) and the OPBI solution are ensured to be consistent, so as to facilitate the subsequent non-solvent induced separation process.

[0045] In some embodiments, in the mixed solution, the mass ratio of sHNT-Li to OPBI is 10%-50%, respectively; the lithium-ion battery separator can contain an appropriate amount of sHNT-Li, so that sHNT-Li is used to improve the diffusion force during the non-solvent phase transformation method to obtain a high-temperature resistant lithium-ion battery separator (OPBI@sHNT-Li) whose microscopic pores are composed of regular finger-like pores and sponge-like pores.

[0046] In a preferred embodiment, the sHNT-Li is a product of sulfonation modification of halloysite nanotubes and then lithiation modification; the solution of the sHNT-Li is a sHNT-Li solution with N-methylpyrrolidone as solvent; the solvent of the OPBI solution is N-methylpyrrolidone; polybenzimidazole has excellent thermal stability, mechanical properties, flame retardancy, etc., and contains polar ether bonds and pyridine structures in the molecular chain. HNTs have excellent mechanical properties, large specific surface area, pore volume, excellent hydrophilicity and easy functionalization. Sulfonate groups and lithium ions are grafted on the surface of sHNT-Li. The introduction of sHNT-Li into the diaphragm can increase the affinity between the diaphragm and the electrolyte, and provide more sites and microscopic channels for the transmission of lithium ions. sHNT-Li is used to change the diffusion force in the non-solvent phase conversion method to obtain a high-temperature resistant lithium-ion battery diaphragm with a microscopic pore structure composed of regular finger-like pores and sponge-like pores. Therefore, in view of the material characteristics of polybenzimidazole and sHNT-Li, the composite of the two is prepared into a separator for use in lithium-ion batteries, which helps to solve the safety issues of lithium-ion batteries caused by the heat resistance, flammability and disordered growth of lithium dendrites of the separator. At the same time, from the perspective of the separator, the electrochemical properties of lithium-ion batteries such as rate, cycle stability (including room temperature and high temperature) are improved, and the polarization of battery electrodes is reduced.

[0047] In some embodiments, the mixing treatment is continuous stirring at room temperature for 15-24 hours; stirring at 60-100° C. for 15-24 hours, so that OPBI and sHNT-Li are evenly mixed, in preparation for preparing a lithium-ion battery separator with better performance.

[0048] In some embodiments, in step S30, the method for removing the solvent from the mixed solution is: placing the substrate coated with the mixed solution in anhydrous methanol for immersion treatment, the immersion treatment is standing at room temperature for 8-15 minutes, and preparing the lithium ion battery separator using a non-solvent induced phase separation process. Since OPBI is insoluble in methanol, sHNT-Li is also insoluble in methanol at room temperature, while NMP or DMSO or DMAC is soluble in methanol, the substrate coated with the mixed solution is allowed to stand at room temperature for 8-15 minutes, and methanol is used to make the mixed solution quickly form a film, and replace NMP or DMSO or DMAC to form pores, so that the prepared lithium ion battery separator has a microscopic pore structure composed of regular finger-like pores and sponge-like pores, which is conducive to the uniform deposition of lithium ions on the anode surface, thereby inhibiting the disordered growth of lithium dendrites and improving the safety of the battery during service.

[0049] In some embodiments, in step S30, after the soaking treatment, a drying treatment is further performed to remove methanol in the pores.

[0050] In some embodiments, the substrate is, but is not limited to, a glass plate.

[0051] In addition, the present invention also provides a lithium-ion battery separator, which is prepared by the preparation method of the lithium-ion battery separator containing sHNT-Li.

[0052] In this embodiment, sulfonated lithiated halloysite nanotubes (sHNT-Li) are introduced into the lithium-ion battery separator, and the sulfonated lithiated halloysite nanotubes (sHNT-Li) are used to improve the diffusion force during the non-solvent phase conversion method to obtain a high-temperature resistant lithium-ion battery separator (OPBI@sHNT-Li) whose microscopic pores are composed of regular finger-like pores and sponge-like pores. The lithium-ion battery separator has excellent thermal stability and flame retardancy, no thermal shrinkage occurs at 200°C, and no obvious combustion phenomenon occurs when placed on a flame; the lithium-ion battery separator has good electrolyte wettability, high electrolyte absorption rate (397%), and high conductivity (1.82mS cm -1 ), good electrochemical stability; the lithium-ion battery separator has a variety of lithium-ion transmission modes, which can improve the transport efficiency of lithium ions between the positive and negative electrodes of the battery; the lithium-ion battery separator has a unique microscopic pore structure composed of regular finger-like pores and sponge-like pores, which can induce lithium ions to pass through the separator more quickly and deposit evenly on the surface of the lithium metal anode, effectively inhibiting the disordered growth of lithium dendrites and improving the safety and electrochemical performance of lithium-ion batteries. The battery assembled using the separator exhibits excellent discharge specific capacity, cycle stability, and rate performance, especially excellent charge and discharge stability at high temperatures; in addition, the polarization degree of the battery electrode is low.

[0053] In some embodiments, the thickness of the lithium ion battery separator containing sulfonated lithiated halloysite nanotubes (sHNT-Li) is 20-40 microns; the lithium ion battery separator at this thickness has excellent thermal stability and can inhibit the disordered growth of lithium dendrites.

[0054] In addition, the present invention also provides a lithium-ion battery, including a positive electrode sheet, a negative electrode sheet and a lithium-ion battery separator containing sulfonated lithiated halloysite nanotubes (sHNT-Li); the lithium-ion battery separator containing sulfonated lithiated halloysite nanotubes (sHNT-Li) is located between the positive electrode sheet and the negative electrode sheet.

[0055] In this embodiment, the LiFePO4 / Li battery assembled with the lithium ion battery separator containing sulfonated lithiated halloysite nanotubes (sHNT-Li) has a peak discharge capacity of 150.2 mAh g at 0.5C. -1 After 200 cycles, the capacity retention rate of the battery is 91.7%. In addition, the LiFePO4 / Li battery assembled with the lithium-ion battery separator containing sulfonated lithiated halloysite nanotubes (sHNT-Li) can also operate at temperatures of 50°C and 90°C with a considerable capacity retention rate; and the battery assembled with the lithium-ion battery separator containing sulfonated lithiated halloysite nanotubes (sHNT-Li) can operate smoothly and safely at high temperatures (such as 50°C and 90°C).

[0056] The following examples are further given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention.

[0057] Example 1

[0058] This embodiment provides a method for preparing a lithium-ion battery separator (OPBI@sHNT-Li composite membrane) containing sulfonated lithiated halloysite nanotubes (sHNT-Li) and a lithium-ion battery, the flow diagram of which is shown in FIG. Figure 1 As shown, the steps include:

[0059] Step S1: dissolving OPBI in NMP to form a uniform OPBI solution;

[0060] The sulfonated lithiated halloysite nanotubes (sHNT-Li) are dissolved in NMP to form a sulfonated lithiated halloysite nanotube (sHNT-Li) solution using NMP as a solvent.

[0061] Step S2: adding the sulfonated lithiated halloysite nanotube (sHNT-Li) solution to the OPBI solution, and continuously stirring at 80° C. for 20 hours to obtain a mixed solution, wherein the mass ratios of sHNT-Li to OPBI in the mixed solution are 10%, 20%, and 30%, respectively.

[0062] Step S3: The obtained mixed solution was coated on a glass plate with a scraper and transferred into anhydrous methanol (MeOH) and allowed to stand for 10 min to obtain a porous film, and then the porous film was dried at room temperature to obtain OPBI@sHNT-Li10, OPBI@sHNT-Li20, and OPBI@sHNT-Li30 composite membranes.

[0063] Step S4: Assembling a lithium-ion battery using the lithium-ion battery separator containing sulfonated lithiated halloysite nanotubes (sHNT-Li).

[0064] Among them, the preparation process of sulfonated lithiated halloysite nanotubes (sHNT-Li) is as follows: 1 gram of halloysite nanotubes (HNTs) is immersed in 4 mol / L hydrochloric acid (HCl) for 6 days for acid activation treatment; the activated HNTs are washed 3 times with deionized water and dried at 80°C under vacuum conditions for 24 hours; the HNTs are mixed with 1 mL of 3-chloropropyltrimethoxysilane (CPTMS) and dispersed in 20 mL of toluene under reflux at 115°C for 8 hours to obtain HNT-Cl; the HNT-Cl is washed 3 times with toluene and deionized water, and then dried at 80°C under vacuum conditions for 24 hours; HNT-Cl was reacted with 1 g of tannic acid (TA) in 20 mL of N,N-dimethylformamide (DMF) at 60°C for 12 hours to obtain the sulfonated product sHNT; the above product sHNT was washed with DMF and deionized water three times and dried at 80°C under vacuum conditions for 24 hours; the sHNT was soaked in hydrochloric acid (HCl) with a pH value of 3 for 3 hours, and then reacted with a lithium hydroxide (LiOH) solution with a pH value of 11 for 12 hours to obtain the product sHNT-Li; the final product sHNT-Li was washed with deionized water three times and dried at 80°C under vacuum conditions for 24 hours.

[0065] For comparison, this embodiment also provides PP (polypropylene) film, OPBI film, and OPBI@HNT20, wherein the preparation methods of OPBI film and OPBI@HNT20 are the same as the preparation method of OPBI@sHNT-Li composite film, both of which adopt the non-solvent phase transfer method.

[0066] The transport mode of lithium ions between the positive and negative electrodes in the battery assembled with OPBI@sHNT-Li composite membrane is schematically shown as follows:

[0067] Figure 2Schematic diagram of lithium ion transport in a battery assembled with sHNT-Li composite separator. There are three main ways for lithium ions to be transported between the positive and negative electrodes: first, through the regular finger-like holes and sponge holes in the separator; second, through the pores of sHNT-Li; and third, through the negatively charged sulfonic acid groups on the surface of sHNT-Li.

[0068] The chemical compositions of HNTs, sHNTs, and sHNT-Li materials were characterized as follows:

[0069] Figure 3 XPS spectra of HNTs, sHNT, and sHNT-Li. Figure 3 a shows the complete XPS spectra of HNTs, sHNTs, and sHNT-Li. By comparing the peak positions of N1s, S2p, and Li1s elements, it can be seen that the sulfonation and lithium modification of HNTs was successfully completed. Figure 3 b and 3c show the locally enlarged spectra of S2p and Li1s elements, respectively.

[0070] The microstructure and elemental composition of HNTs and sHNT-Li were characterized as follows:

[0071] Figure 4 TEM images of HNTs and sHNT-Li. It can be seen from the results that the main structure of the nanotubes was not destroyed during the modification process.

[0072] Figure 5 TEM and EDS images of sHNT-Li. Figure 5 The results of bd show the energy spectrum distribution of O, Si and Al elements in sHNT-Li, indicating that the main elements of the modified HNTs have not changed. Figure S5e and f show the EDS spectra of N and S elements, respectively, proving that the sulfonation and lithiation modification of HNTs was successfully completed.

[0073] The thermal stability and chemical composition of HNTs, sHNT-Li and various separators were characterized as follows:

[0074] Figure 6 TGA curves (a) and FT-IR spectra (b) of HNTs and sHNT-Li, TGA curve of the separator (c), and FT-IR spectra of the separator and sHNT-Li (d). Figure 6 As shown in (a), the weight loss between 450°C and 500°C may be due to the dehydration process of hydroxyl groups in the HNTs tube wall, while the weight loss of sHNT-Li between 300 and 450°C is due to the decomposition of taurine, which indicates that taurine is successfully grafted onto the HNTs surface. Figure 6 b shows the infrared spectra of HNTs and sHNT-Li, 3622 cm-1 and 3694cm -1 The peak at 1097 cm-1 was attributed to the stretching vibration peak of the internal hydroxyl group and the external surface hydrogen. -1 The peak of Si-O stretching vibration is 912 cm -1 The -OH stretching vibration peak is at 536 cm -1 The peak at 1640 cm is the stretching vibration peak of Al-O. -1 、1402cm -1 and 1010cm -1 The peaks at 4 and 7 belong to the stretching vibration peaks of NH, S=O and SO, respectively, proving that the -SO3Li group was successfully grafted onto the HNTs. Figure 6 c It can be seen that at around 300°C, the weight of the PP diaphragm decreases rapidly due to the thermal decomposition of the polyolefin main chain. In contrast, the weight loss of the OPBI diaphragm, OPBI@HNTs diaphragm, and OPBI@sHNT-Li series diaphragm mainly occurs at around 500°C, and the weight loss at around 220°C is mainly due to the evaporation of the solvent NMP and water molecules. The OPBI@sHNT-Li series diaphragm can still maintain a weight retention rate of more than 60% at 700°C. Figure 6 d is the infrared curve of OPBI, OPBI@sHNT-Li20 and sHNT-Li. -1 and 1436cm -1 The bands at 1165cm are the stretching vibration peaks of C=N and benzimidazole. -1 The peak at 3694cm is the vibration peak of the ether bond, which is the typical structural characteristic peak of OPBI. -1 and 3622cm -1 The peak at 1097 cm-1 belongs to the -OH stretching vibration peak, while -1 and 536cm -1 The peaks belong to the stretching vibration peaks of Si-O and Al-OAl-O, which are the main structural characteristic peaks of HNTs found on sHNT-Li and OPBI@sHNT-Li20. In addition, the 1402cm -1 and 1010cm -1 The peaks at belong to the characteristic peaks of S=O and SO, respectively, indicating the presence of -SO3H groups. In summary, it can be inferred that sHNT-Li20 has been successfully introduced into the composite membrane.

[0075] The surface morphology and cross-sectional morphology of the diaphragm were characterized as follows:

[0076] Figure 7SEM images of PP film, OPBI film, OPBI@HNT20 composite film, OPBI@sHNT-Li10 composite film, OPBI@sHNT-Li20 composite film, and OPBI@sHNT-Li30 composite film. Figure 7 The cross-section of the separator prepared by the non-solvent induced phase separation (NIPS) method shown in (h, i, p, q, r) shows a structure with coexistence of sponge-like and finger-like pores, which makes the OPBI membrane, OPBI@HNT20 composite membrane, OPBI@sHNT-Li10 composite membrane, OPBI@sHNT-Li20 composite membrane, and OPBI@sHNT-Li30 composite membrane have higher porosity, so that more electrolyte can be absorbed. Compared with the pure OPBI separator, the composite separator with pure halloysite nanotubes (HNTs) added (i.e., OPBI@HNT20) has an increased volume of finger-like pores and a decreased volume of sponge-like pores in the cross-section, which is due to the diffusion force formed by the mutual diffusion of non-solvent MeOH and solvent N-methylpyrrolidone (NMP) when the slurry is immersed in methanol (MeOH). These diffusion forces reach their maximum in the direction perpendicular to the membrane surface, causing the HNTs dispersed in the slurry to be vertically arranged under the action of these forces. The vertically aligned HNTs blocked the lateral diffusion force, allowing the vertical diffusion force to continue to form finger-like pores perpendicular to the membrane surface, which can be clearly observed as an increase in volume in the cross-sectional images. Figure 7 (pr) is the morphology of the upper and lower surfaces of the OPBI@sHNT-Li10 composite membrane, the OPBI@sHNT-Li20 composite membrane, and the OPBI@sHNT-Li30 composite membrane. It can be seen that with the increase in the sHNT-Li ratio, the diffusion force becomes more concentrated and distributed perpendicular to the membrane surface, resulting in an increase in the volume of the finger-like pores in the OPBI@sHNT-Li membrane. In addition, the -SO3Li groups grafted on the surface of HNTs repel each other, reducing agglomeration and making the dispersion more uniform, which is reflected in the denser pores and larger finger-like pore diameters of OPBI@sHNT-Li20 compared to OPBI@HNT20. However, when the proportion of sHNT-Li reaches 30%, the nanotubes tend to agglomerate to form clusters of different sizes, which affects the direction and size of the diffusion force, resulting in uneven pore distribution and size on both sides of the membrane, such as Figure 7 (l, o). Therefore, when preparing lithium-ion battery (LIB) separators, the amount of sHNT-Li introduced should be moderate.

[0077] The anti-bending properties, electrolyte wettability and contact angle of the separator are characterized as follows:

[0078] Figure 8The results of the bending resistance, electrolyte wettability, and contact angle of PP film, OPBI film, OPBI@HNT20 composite film, OPBI@sHNT-Li10 composite film, OPBI@sHNT-Li20 composite film, and OPBI@sHNT-Li30 composite film are shown in Figure 2. The OPBI@sHNT-Li20 composite film can still maintain its original shape after repeated bending without damage or wrinkles. It has good mechanical strength and can meet the requirements of lithium battery assembly for membrane strength. Compared with PP and OPBI membranes, the OPBI@sHNT-Li composite membrane has better wetting properties. Among them, the OPBI@sHNT-Li20 membrane has the best wetting properties, with an electrolyte absorption rate of up to 397% and a contact angle of only 11.8°. This is due to the high porosity of the OPBI@sHNT-Li20 composite membrane and the hydrophilic groups in sHNT-Li. Due to the introduction of additional hydrophilic groups -SO3Li and higher porosity, OPBI@sHNT-Li20 has a higher electrolyte absorption rate compared with OPBI@HNT20.

[0079] The heat resistance and flame retardancy of the diaphragm are characterized as follows:

[0080] Fig. 9 The heat resistance (a) of PP film, OPBI film, OPBI@HNT20 composite film, OPBI@sHNT-Li10 composite film, OPBI@sHNT-Li20 composite film, and OPBI@sHNT-Li30 composite film, and the flame retardancy (b) of PP film and OPBI@sHNT-Li20 composite film. Fig. 9 a The results show that the PP separator shrinks significantly at 150°C and completely melts at 200°C, while the OPBI and OPBI@sHNT-Li separators do not shrink significantly at 200°C, indicating that the thermal stability of the OPBI and OPBI@sHNT-Li separators is sufficient to support the operation of the battery at high temperatures. Fig. 9 b The results show that the PP separator melted and curled before contacting the flame, and was immediately ignited once it contacted the flame. The OPBI@sHNT-Li20 separator only curled slightly before contacting the flame and carbonized into black carbide in the center of the flame. The visible carbide remained until the end of combustion, which proves the ability of the OPBI@sHNT-Li20 separator to withstand high temperatures and its excellent flame retardancy.

[0081] The electrical properties and stability of the diaphragm were characterized as follows:

[0082] Fig.10The AC impedance of a battery assembled by a separator sandwiched between two steel plates (a), the interfacial resistance of a symmetrical battery assembled by a separator sandwiched between two lithium electrodes (b), the linear sweep voltammetry (LSV) test results of a battery assembled by a lithium iron phosphate positive electrode and a separator sandwiched between steel plates (c), and the lithium deposition / stripping cycle stability of a battery assembled by a separator sandwiched between two lithium electrodes (d). Fig.10 As shown in a, in the electrochemical impedance spectroscopy (EIS) test of the SS / membrane / SS battery assembly, the bulk resistance (R b ) is significantly lower than that of PP and OPBI membranes. This may be due to the strong affinity between the bulk resistance of OPBI@sHNT-Li20 membrane and the electrolyte and better interface stability. More importantly, OPBI@sHNT-Li20 membrane has diversified lithium ion transmission channels, which can improve the transport efficiency of lithium ions between the positive and negative electrodes of the battery. The conductivity of PP membrane, OPBI membrane and OPBI@sHNT-Li20 membrane is 0.63mS·cm - 1.0.82mS·cm - 1.1.82mS·cm - 1, the latter is 2.9 times of the former. Fig.10 b shows the EIS measurement results of Li / Li symmetric cells with different separators. The interfacial resistance of the OPBI separator is lower than that of the PP separator. It is worth noting that the interfacial resistance of the OPBI@sHNT-Li20 separator is further significantly reduced. The main reasons are: the imidazole structure in the OPBI separator helps to improve the affinity between the separator and the electrolyte. In addition, the OPBI separator has a larger porosity; the pore structure of the OPBI@sHNT-Li20 separator, which combines regular finger pores and sponge pores, and the -OH and -SO3Li groups on the surface of sHNT-Li20 further enhance the affinity between the separator and the electrolyte, ensuring full contact with the lithium metal electrode and providing a channel for the efficient transport of lithium ions, thereby reducing the interfacial resistance between the separator-electrolyte system and the lithium metal electrode. Fig.10 c shows the linear sweep voltammetry (LSV) test results of SS / PP / LiFePO4 and SS / OPBI@sHNT-Li20 / LiFePO4 batteries, indicating that the polarization voltage of PP, OPBI and OPBI@sHNT-Li20 membranes gradually increases, which indicates that the OPBI@sHNT-Li20 composite membrane has a wider electrochemical stability range and better anode stability, ensuring stable operation even at higher voltages. Fig.10As shown in Figure d, the lithium deposition and stripping performance of lithium metal electrodes during the cycling process was simulated. Specifically, Li / PP / Li and Li / OPBI@sHNT-Li20 / Li batteries were assembled and cycled for 1100 h at a current density of 0.5 mA cm -2 It was observed that the Li / PP / Li cell exhibited an unstable polarization voltage within the first 200 h, reaching a maximum of 288.9 mV. In contrast, the Li / OPBI@sHNT-Li20 / Li cell maintained excellent voltage stability throughout the 1100 h cycle.

[0083] The effect of the diaphragm in inhibiting the growth of lithium dendrites on the surface of the anode lithium sheet was characterized as follows:

[0084] Fig.11 The SEM image of the surface of a pure lithium sheet (a), the SEM image of the surface of the anode lithium sheet after 200 charge and discharge cycles of the battery assembled with PP film, OPBI film, and OPBI@sHNT-Li20 composite film (bd), and the schematic diagram of lithium ion deposition and lithium dendrite growth on the surface of the anode lithium sheet in the battery assembled with PP film and OPBI@HNT20 (e). During the operation of lithium-ion batteries, the anode surface may form a sharp protrusion due to the disordered growth of lithium dendrites, which can pierce the separator and pose a threat to battery safety. Fig.11 (ad) show the surface morphology of the lithium anode, where Fig.11 a shows the surface of pure lithium, Fig.11 (bd) show the surface of lithium metal electrode of batteries assembled with PP separator, OPBI separator and OPBI@sHNT-Li20 separator after 200 cycles. Compared with PP separator and OPBI separator, the surface of lithium anode of battery assembled with OPBI@sHNT-Li20 separator is the smoothest after 200 cycles. The main reasons are: first, the multi-channel transport mechanism of lithium ions in OPBI@sHNT-Li20 separator reduces the resistance during the transport process, making lithium ion transport efficient and orderly; second, the microscopic pores composed of regular finger-like pores and sponge-like pores in OPBI@sHNT-Li20 separator are conducive to the efficient transport of lithium ions, and can guide the uniform deposition of lithium ions on the surface of the anode lithium sheet, inhibiting the disordered growth of lithium dendrites. In summary, OPBI@sHNT-Li20 separator can enhance the safety and electrochemical performance of lithium-ion batteries.

[0085] The cycle stability and rate performance of the battery are characterized as follows:

[0086] Fig.12The charge and discharge curves (a, b) of the battery assembled with PP diaphragm and OPBI@sHNT-Li20 composite diaphragm, and the cycle stability and rate performance (c, d) of the LiPO4 / Li half-cell. Fig.12 From a and b, it can be seen that the electrode polarization of the battery assembled with OPBI@sHNT-Li20 composite membrane is smaller. Fig.12 c It can be seen that the initial discharge specific capacities of the batteries assembled with PP film, OPBI film, OPBI@HNT20 composite film, OPBI@sHNT-Li10 composite film, OPBI@sHNT-Li20 composite film, and OPBI@sHNT-Li30 composite film are 128.32 mAh g -1 、133.38mAh·g -1 、132.75mAh·g -1 、145.85mAh·g -1 、150.2mAh·g -1 , 129mAh·g -1 The battery assembled with OPBI@sHNT-Li20 composite membrane has good cycle stability, with a capacity retention rate of 91.7% after 200 cycles, while the capacity retention rate of the battery assembled with PP diaphragm is only 78.6% after 200 cycles. This difference is attributed to the microscopic pore structure, composition, porosity, electrolyte absorption rate and other properties of the diaphragm. Fig.12 d It can be seen that the battery assembled with OPBI@sHNT-Li20 composite membrane has the best rate performance. This can also be attributed to the microscopic pore structure, composition, porosity, electrolyte absorption rate and other properties of the separator.

[0087] The cycling stability of the battery at high temperature is characterized as follows:

[0088] Fig.13 The discharge curves of the battery assembled with PP diaphragm and OPBI@sHNT-Li20 composite diaphragm at 50℃ and 90℃ at 0.5C discharge. It can be seen that compared with the battery assembled with PP membrane, the battery assembled with OPBI@sHNT-Li20 composite membrane has a stable discharge capacity retention rate at 50℃ and 90℃ at 0.5C discharge, and the battery can operate safely and stably.

[0089] In summary, the present invention provides a lithium ion battery separator containing sulfonated lithiated halloysite nanotubes (sHNT-Li), a preparation method thereof, and a lithium ion battery. The preparation method comprises the steps of: providing an OPBI solution and a solution containing sulfonated lithiated halloysite nanotubes (sHNT-Li); mixing the OPBI solution and the solution containing sulfonated lithiated halloysite nanotubes (sHNT-Li) to obtain a mixed solution; coating the mixed solution on a substrate, and removing the solvent in the mixed solution to obtain a lithium ion battery separator containing sulfonated lithiated halloysite nanotubes (sHNT-Li); and assembling a lithium ion battery using the lithium ion battery separator containing sulfonated lithiated halloysite nanotubes (sHNT-Li). The present invention introduces sulfonated lithiated halloysite nanotubes (sHNT-Li) into the battery separator, thereby increasing the affinity between the separator and the electrolyte, and providing more sites and microscopic channels for the transmission of lithium ions; the sulfonated lithiated halloysite nanotubes (sHNT-Li) are used to change the diffusion force in the non-solvent phase transformation process to obtain a high-temperature resistant lithium-ion battery separator with a microscopic pore structure consisting of regular finger-like pores and sponge-like pores. The separator has good wettability to the electrolyte, high electrical conductivity, and good electrochemical stability. The unique pore structure can induce lithium ions to pass through the separator more quickly and deposit evenly on the surface of the lithium metal anode, effectively inhibiting the disordered growth of lithium dendrites, and improving the safety and electrochemical performance of lithium-ion batteries. The battery assembled using the separator exhibits excellent discharge specific capacity, cycle stability, and rate performance, especially excellent charge and discharge stability at high temperatures; in addition, the battery electrode polarization degree is low.

[0090] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing a lithium ion battery separator containing modified halloysite nanotubes, characterized in that: Includes steps: providing an OPBI solution and a solution of sulfonated lithiated halloysite nanotubes (sHNT-Li); Mixing the OPBI solution and the sulfonated lithiated halloysite nanotube (sHNT-Li) solution to obtain a mixed solution; The mixed solution is coated on a substrate, and the solvent in the mixed solution is removed to obtain a lithium ion battery separator containing sulfonated lithiated halloysite nanotubes (sHNT-Li).

2. The method for preparing a lithium ion battery separator containing modified halloysite nanotubes according to claim 1, characterized in that: The modified halloysite nanotubes are sulfonated lithiated halloysite nanotubes (sHNT-Li), and the sulfonated lithiated halloysite nanotubes (sHNT-Li) are prepared by first subjecting halloysite nanotubes (HNTs) to sulfonation modification and then to lithiation modification.

3. The method for preparing a lithium ion battery separator containing modified halloysite nanotubes according to claim 1, characterized in that: The solvent of the sulfonated lithiated halloysite nanotube (sHNT-Li) solution and the solvent of the OPBI solution are jointly selected from one or more of N-methylpyrrolidone, dimethyl sulfoxide, and N,N-dimethylacetamide.

4. The method for preparing a lithium ion battery separator containing modified halloysite nanotubes according to claim 1, characterized in that: In the mixed solution, the mass ratio of the sHNT-Li to the OPBI is 10%-50% respectively.

5. The method for preparing a lithium ion battery separator containing modified halloysite nanotubes according to claim 2, characterized in that: The preparation process of the sulfonated lithiated halloysite nanotubes (sHNT-Li) is as follows: first, the halloysite nanotubes (HNTs) are acid-activated by hydrochloric acid (HCl); then, the acid-activated halloysite nanotubes (HNTs) are mixed with 3-chloropropyltrimethoxysilane (CPTMS) to obtain HNT-Cl; then, the HNT-Cl is reacted with tannic acid (TA) to obtain the sulfonated product sHNT; finally, the sHNT is soaked in hydrochloric acid (HCl) and reacted with a lithium hydroxide (LiOH) solution to obtain the product sHNT-Li.

6. The method for preparing a lithium ion battery separator containing modified halloysite nanotubes according to claim 1, characterized in that: The mixing treatment is carried out by continuously stirring at 60-100° C. for 15-24 hours.

7. The method for preparing a lithium ion battery separator containing modified halloysite nanotubes according to claim 1, characterized in that: The method for removing the solvent in the mixed solution is: placing the substrate coated with the mixed solution in anhydrous methanol for immersion treatment, and the immersion treatment is standing at room temperature for 8-15 minutes.

8. A lithium ion battery separator containing modified halloysite nanotubes, characterized in that: The lithium-ion battery separator containing modified halloysite nanotubes is prepared by the preparation method according to any one of claims 1 to 7, wherein the microscopic pores of the separator are composed of regular finger-like pores and sponge-like pores.

9. The lithium ion battery separator containing modified halloysite nanotubes according to claim 8, characterized in that: The thickness of the lithium ion battery separator containing modified halloysite nanotubes is 20-40 microns.

10. A lithium ion battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and a lithium ion battery separator containing modified halloysite nanotubes as described in any one of claims 8 to 9; the lithium ion battery separator containing modified halloysite nanotubes is located between the positive electrode sheet and the negative electrode sheet.

Citation Information

Cited By

  • Lithium battery diaphragm and preparation method thereof

    CN120691045A

  • A lithium battery separator and a method of making the same

    CN120691045B